2014
DOI: 10.1017/s1368980014003012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Dutch school-based education programme ‘Taste Lessons’ on behavioural determinants of taste acceptance and healthy eating: a quasi-experimental study

Abstract: Objective: To assess the effect of the Dutch school-based education programme 'Taste Lessons' on children's behavioural determinants towards tasting unfamiliar foods and eating healthy and a variety of foods. Design: In a quasi-experimental study design, data on behavioural determinants were collected at baseline, four weeks and six months after the intervention in both the intervention and control group. Children completed consecutively three questionnaires in which knowledge, awareness, skills, attitude, emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 39 publications
(53 reference statements)
1
39
0
1
Order By: Relevance
“…In contrast to some studies, the current researchers found neither a reduced food neophobia, 3,4 a generic attitude toward novel foods, nor a subjective norm perceived by teachers. 5 Together, results seem to indicate that VERTI-CAL's effect is specific to vegetables and primarily affects student cognitions and attitudes directly.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast to some studies, the current researchers found neither a reduced food neophobia, 3,4 a generic attitude toward novel foods, nor a subjective norm perceived by teachers. 5 Together, results seem to indicate that VERTI-CAL's effect is specific to vegetables and primarily affects student cognitions and attitudes directly.…”
Section: Discussionmentioning
confidence: 82%
“…4 The current authors also observed a more positive attitude in the younger age group whereas a longer intervention did not. 5 These comparisons show that content has a critical role in intervention success and can negate reductions in duration. The difference in the content of VERTICAL, compared with those programs, is that it focused on targeting only vegetables and was based on evidencebased insights about children's development of vegetable acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the pupils were offered an opportunity to get to know vegetables by using the senses of smell, taste, touch, vision and hearing (the Sapere method). Earlier interventions using the Sapere food education method in nutrition education have also been successful at encouraging children to try new, unfamiliar foods and expand their food repertoire and willingness to choose and taste vegetables . The Tools for Feeling Good curriculum consisting of 11 active lectures was carried out by teachers over the course of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recent articles that were published after the Future for Food Conference highlighted the impact of sensory-based food education. The Dutch school-based program showed an increase in the number of known and tasted foods (Battjes-Fries et al, 2015). In UK, the non-taste sensory activity program increased the willingness to try vegetables at the mealtime taste test (Dazeley & Houston-Price, 2015).…”
Section: Discussionmentioning
confidence: 99%